STRATEGI E-COMMERCE DAN PEMASARAN DIGITAL DALAM PENGEMBANGAN USAHA CAMILAN PANGSIT COKELAT EAT MEE - Berlian Nursyanti Mahardika; Neng Silvi Miladiah; Helen Veranika; Ati Yulyanti; Wulan Meliyawati; Ipan Ipan (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The rapid digital transformation has significantly impacted Micro, Small, and Medium Enterprises (MSMEs), shifting consumer behavior towards online product search. This presents both challenges and opportunities for the snack industry, which faces intense competition. This study addresses the limited empirical research on digital channel effectiveness in the fast-moving snack sector. The research aims to examine the e-commerce and digital marketing strategies of "Eat Mee" chocolate dumplings and evaluate their contribution to business development. Using a qualitative descriptive approach with a case study method, the research focused on "Eat Mee" in Serang, Banten, utilizing participatory observation and sales data from June 2025. Findings indicate that while e-commerce positively impacts sales, offline channels (Cash on Delivery) still dominate (Rp358,000 vs. Rp105,000 from Shopee), with no transactions via the personal website. This highlights the importance of consistent promotion and internal operational readiness alongside digital platforms. The study concludes that "Eat Mee" needs to optimize its digital marketing strategies for broader market reach while maintaining strong offline sales.